Predictors of health-related quality of life in a large cohort of adult patients living with sickle cell disease in France: the DREPAtient study - Yaya, Issifou; Pourageaud, Adrien; Derbez, Benjamin; Odièvre, Marie-Hélène; Oudin Doglioni, Damien; Podevin, Marieke; Thomas, Gaëlle; Yombo-Kokule, Lisa; Godart, Christian; Lepetit, Maryannick; Cassubie-Mercier, Tania; Galacteros, Frederic; et al. (Frontiers in Public Health, 2024)
Background Sickle cell disease (SCD) is an inherited autosomal recessive disorder, causing a range of symptoms and acute and/or chronic complications that affect the quality of life. This study aimed to assess health-related quality of life (HRQoL) and to identify associated factors in adult patients with SCD in France. Methods DREPAtient is a cross-sectional, multicentre study conducted from June 2020 to April 2021 in France, and in certain French overseas territories where SCD is highly prevalent. Sociodemographic and clinical data were collected online. HRQoL was assessed by SF-36 French version. HRQoL determinants were identified using multivariable linear regression analysis. Results Five hundred and seventy participants were included, mostly female (68.9%), with a mean age of 33.3 (±10.7) years. The highest mean score HRQoL was found in the Physical functioning domain (67.5±21.8), and the lowest mean score in the General Health perception domain (37.7±20.3). The mean score of the physical composite (PCS) and mental composite (MCS) of SF-36 summary scores was 40.6±8.9 and 45.3±9.8, respectively. Participants receiving oxygen therapy (β= -3.20 [95%CI: -5.56; -0.85]), those with a history of femoral osteonecrosis (-3.09 [-4.64; -1.53]), those hospitalized for vaso-occlusive crisis (VOC) or acute chest syndrome (ACS) (-2.58 [-3.93; -1.22]), those with chronic complications (-2.33 [-4.04; -0.62]), female participants (-2.17 [-3.65; -0.69]), those with psychological follow-up (-2.13 [-3.59; -0.67]), older participants (-1.69 [-3.28; -0.09]), and those receiving painkillers (-1.61 [-3.16; -0.06]) reported worse PCS score. By contrast, those who had completed secondary or high school (4.36 [2.41; 6.31]), and those with stable financial situation (2.85 [0.94; 4.76]) reported better PCS scores. Worse MCS scores were reported among participants with psychological follow-up (-2.54 [-4.28; -0.80]), and those hospitalized for VOC/ACS in the last 12 months (-2.38 [-3.99; -0.77]), while those who had relatives’ support (5.27 [1.92; 8.62]), and those with stable financial situation (4.95 [2.65; 7.26]) reported better MCS score. Conclusion Adults with major SCD reported poor physical and mental HRQoL scores. Hospitalization for VOC/ACS, chronic complications, painkillers use, perceived financial situation and support from relatives are important predictors of HRQoL in SCD patients. Interventions to improve HRQoL outcomes SCD should be considered.